Data Transmission System based on PCI bus & fiber-optical link - Hu Yongbing; Zhou Yunfei; Wei Xingyun (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
To achieve real-time monitoring and control of a measurement and control system is often applied in industrial control, with the host computer. In accordance with the requirements of real-time data transmission, a hardware system with a FPGA as the main control unit for the logical interface, the PCI bus and the high-speed fiber-optic link as the data transmission channels communicating with the host computer and a measurement control system respectively is built; the debugging are completed for the HSSL IP core and the PCI interface module; the system test is fulfilled among the host computer, the data transmission board and the specific monitoring control board. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2212